2021
DOI: 10.1365/s42681-021-00025-6
|View full text |Cite
|
Sign up to set email alerts
|

The positive connection between dark triad traits and leadership levels in self- and other-ratings

Abstract: People with high dark triad tendencies are often found in leadership positions. Yet research is lacking on whether dark triad personality traits positively correlate with the height of leadership levels (no leadership position, low-level leaders, high-level leaders, head and founder of the company). To explore this relationship between the dark triad and these leadership levels, three studies (NGermany = 137; NHungary = 333; NBothCountries = 355) were conducted, to measure dark triad scores for each leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…Past research (e.g., Blair et al, 2017 ) showed that there are several unethical leadership behaviors in which leaders with narcissism are likely to be engaged. Still, it is commonly thought that some characteristics of narcissism may be helpful in being hired as a leader (Diller et al, 2021 ).…”
Section: Is Being Low On Narcissism a Resource For A Successful Leade...mentioning
confidence: 99%
“…Past research (e.g., Blair et al, 2017 ) showed that there are several unethical leadership behaviors in which leaders with narcissism are likely to be engaged. Still, it is commonly thought that some characteristics of narcissism may be helpful in being hired as a leader (Diller et al, 2021 ).…”
Section: Is Being Low On Narcissism a Resource For A Successful Leade...mentioning
confidence: 99%
“…In Study 1, participants were randomly assigned to the conditions: control condition (n = 76; non-DT leader of another team), experimental condition with a DT leader of another team (n = 60; DTdistant), DT leader of own team (n = 74; DTnear) and a DT leader of another team in another company (n = 45; DTverydistant). The DT description and a manipulation check were created based on the Dirty Dozen Scale (Jonason & Webster, 2010) with some additions based on the descriptions of the DT leader in the study by Diller et al (2021) (see Appendix 2). Items of the manipulation check ranged on a five-point Likert scale from 1 (not at all) to 5 (extremely) (see Appendix 2).…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…Several studies have shown that individuals with high tendencies toward the Dark Triad are more likely found in leadership positions (Babiak et al, 2010;Brunell et al, 2008;Diller et al, 2021;Grijalva et al, 2015;Harms et al, 2011;Landay et al, 2019;Palmen et al, 2021). The Dark Triad consists of subclinical [Subclinical dark triad behavior consists of the "same patterns of dysfunctional behaviors, affects, and cognitions; however, the pervasiveness and levels of impaired functioning are not as extreme because the individual manifests the symptoms at a commensurately lower level and rate.…”
Section: Like Moths Into the Fire How Dark Triad Leaders Can Be Both ...mentioning
confidence: 99%
See 2 more Smart Citations